TALABALARDÍŃ SOCIALLÍQ BEYIMLESIWINDE KOMMUNIKATIV KÓNLIKPELERDI RAWAJLANDÍRÍWDÍŃ ÁHMIYETI - Risnazarova, A.R. (SCIENCE and SOCIETY, 2024)
The article provides examples of the development of communication skills among students as a means of social adaptation. The reasons and factors of their occurrence are also given.